The Revision of the Cooperation Model in the Case of the FM-Alliance - Weise, Andreas Dittmar; Schultz, Charles Albino; Trierweiller, Andréa Cristina; Rocha, Rudimar Antunes da (Revista ADM.MADE, 2011)
There are several concepts and types of business strategies used on the last decades. However, a lot of these strategies aren"t applicable for cooperation"s. The only existing way to determinate the situation of the cooperation consists by using the strategic model of cooperation. The purpose of this study consists in verifying the strategic model of cooperation by analyzing the cooperation "FM-Alliance". Methodologically, this study qualifies as empirical, theoretical and a case study. A questionnaire is developed for the application of this model and after that applies it to a group of companies that work in cooperation FM Alliance. As a result it was obtained that the FM Alliance with six partners is unfavorable for the cooperation, because one of the partner companies is dormant. Alternatively, the dormant partner leaves the cooperation. That gives the cooperation now possibilities to enter in new markets and core competences.